Management of the coordination process in socio-technical system - Girchenko, L.A.; Doroshenko, А.Yu.; Ziubrytska, Y.V. (Проблеми програмування, 2020)
The article considers the theoretical principles of management of the coordination process in the socio-technical system; the base of corporate knowledge of the IT company is investigated; the problems of using the company's corporate knowledge base are analyzed; the directions of transformation of the corporate knowledge base are outlined; the types of spaces in the base of corporate knowledge and methods of their management are defined. The main characteristics of the socio-technical system are considered, which ensure success in the intensified competition and at the same time characterize the level of development of the new managerial thinking. The study clarifies the effects of information technology on the activities of human organizations and markets, the importance of coordination in many types of systems. The article identifies the main components of coordination, forecasts about the possible consequences of reducing coordination costs. Considerable attention in the article is paid to the peculiarities of construction and adjustment of management processes of corporate knowledge bases of socio-technical systems; methodological approaches and practice of ensuring the management of the coordination process in the socio-technical system. there is a tendency to accelerate the emergence of various species. The article identifies the main directions of transformation of the corporate knowledge base, outlines the prospects for further development of management of the coordination process in the socio-technical system. As a result, the types of spaces in the corporate knowledge base are identified and recommendations for methods of managing them are offered. У статті розглядаються теоретичні засади управління процесом координації у соціотехнічній системі; досліджено базу корпоративних знань ІТ-компанії; проаналізовано проблеми користування базою корпоративних знань компанії; накреслено напрями перетворення бази корпоративних знань; визначено типи просторів у базі корпоративних знань та методи керування ними. Розглянуто основні характеристики соцiотехнiчної системи, якi забезпечують успiх у загостренiй конкурентнiй боротьбi i одночасно характеризують рiвень розвитку нового управлiнського мислення. З проведеного дослідження стає зрозумілим наслідки впливу інформаційних технологій на діяльність людських організаціях та ринки, важливість координації у багатьох видах систем. У статті визначено основні компоненти координації, здійснено прогнози про можливі наслідки скорочення координаційних витрат. Значну увагу в статті приділяється особливостям побудови та налагодження процесів керування базами корпоративних знань соціотехнічних систем; методичним підходам і практиці забезпечення керування процесом координації у соціотехнічній системі. Прослідковується тенденція до прискорення появи різноманітних видів. Також визначено основні напрями перетворення бази корпоративних знань, окреслено перспективи подальшого розвитку керування процесом координації у соціотехнічній системі. В результаті визначено типи просторів у базі корпоративних знань та запропоновано рекомендації щодо методів керування ними.